Cellular Potts Models - Scianna, Marco; Preziosi, Luigi (Chapman and Hall/CRC, 2013)
A flexible, cell-level, and lattice-based technique, the cellular Potts model accurately describes the phenomenological mechanisms involved in many biological processes. Cellular Potts Models: Multiscale Extensions and Biological Applications gives an interdisciplinary, accessible treatment of these models, from the original methodologies to the la.
Online resource; Title from title page (viewed March 26, 2013)
Keywords: Biological models; Biology -- Mathematical models; Biomathematics; Cytology; Stochastic processes; Modèles biologiques; Biologie; Modèles mathématiques; Biomathématiques; Cytologie; Processus stochastiques; Biology; Mathematical models